Autophagy-Inducing Factor Atg1 Is Required for Virulence in the Pathogenic Fungus Candida glabrata - Shimamura, Shintaro; Miyazaki, Taiga; Tashiro, Masato; Takazono, Takahiro; Saijo, Tomomi; Yamamoto, Kazuko; Imamura, Yoshifumi; Izumikawa, Koichi; Yanagihara, Katsunori; Kohno, Shigeru; Mukae, Hiroshi (Frontiers in Microbiology, 2019)
Candida glabrata is one of the leading causes of candidiasis and serious invasive infections in hosts with weakened immune systems. C. glabrata is a haploid budding yeast that resides in healthy hosts. Little is known about the mechanisms of C. glabrata virulence. Autophagy is a ‘self-eating’ process developed in eukaryotes to recycle molecules for adaptation to various environments. Autophagy is speculated to play a role in pathogen virulence by supplying sources of essential proteins for survival in severe host environments. Here, we investigated the effects of defective autophagy on C. glabrata virulence. Autophagy was induced by nitrogen starvation and hydrogen peroxide (H2O2) in C. glabrata. A mutant strain lacking CgAtg1, an autophagy-inducing factor, was generated and confirmed to be deficient for autophagy. The Cgatg1∆ strain was sensitive to nitrogen starvation and H2O2, died rapidly in water without any nutrients, and showed high intracellular ROS levels compared with the wild-type strain and the CgATG1-reconstituted strain in vitro. Upon infecting mouse peritoneal macrophages, the Cgatg1∆ strain showed higher mortality from phagocytosis by macrophages. Finally, in vivo experiments were performed using two mouse models of disseminated candidiasis and intra-abdominal candidiasis. The Cgatg1∆ strain showed significantly decreased CFUs in the organs of the two mouse models. These results suggest that autophagy contributes to C. glabrata virulence by conferring resistance to unstable nutrient environments and immune defense of hosts, and that Atg1 is a novel fitness factor in Candida species.